Perceptions of e-cigarette harm among cancer survivors: Findings from a nationally representative survey. (June 2022) - Bjurlin, Marc A.; Basak, Ramsankar; Zambrano, Ibardo; Schatz, Daniel; El Shahawy, Omar; Sherman, Scott; Matulewicz, Richard S.
Abstract: Background: The growth in e-cigarette use may be driven by the perception that they are a safer, healthier alternative to conventional cigarettes. However, their long-term health implications are not well known and use is discouraged by most cancer societies. It is currently unclear how cancer survivors perceive the risks associated with e-cigarette and how this may influence use in this population. Methods: A cross-sectional analysis was conducted using the Health Information National Trends Survey (HINTS) (Years 2017–2019). Our primary study outcome was the perception of harm associated with e-cigarettes compared to traditional cigarettes among adults with and without a self-reported history of cancer. We used logistic regression analyses assessing the association of a cancer history with the perception that e-cigarettes are as much or more harmful than cigarettes. Results: A total of 11, 846 respondents (weighted population estimate 243, 728, 483) were included. Of these, 26.6% reported a history of cancer. The proportion of cancer survivors who perceived e-cigarettes to be as much or more harmful than conventional cigarettes was similar to non-cancer respondents (70.6% vs 68.3%, P = 0.35). There was no difference in perception of harm among cancer and non-cancer respondents, adjusted for sociodemographic factors (OR 0.82, 95% CI 0.6–1.1). Past (OR 9.06, 95% Cl 5.06–16.20) and never e-cigarette use (OR 23.40, 95% Cl 13.56–40.38) as well as having a history of cardiopulmonary disease (OR 1.28, 95% Cl 1.05–1.56) was associated with higher odds of perceiving e-cigarettes to be as much or more harmful. Conclusion: Cancer survivors commonly perceive e-cigarettes to be as much or more harmful than traditional cigarettes though these findings are similar to perceptions among adults without a history of cancer. There is a strong association with avoidance of e-cigarette products among those who perceive them to be harmful. Highlights: Use of electronic cigarettes is rapidly increasing including among cancer survivors. The growth in e-cigarette use may be driven by the perception that they are a safer alternative to conventional cigarettes. E-cigarette use is discouraged by most cancer societies. It is important to understand the perceived risks associated with e-cigarettes among the cancer population. We found no differences in the perception of e-cigarette harm observed between those with and without a history of cancer. There is a strong association with avoidance of e-cigarette products among those who perceive them to be harmful.